2022
DOI: 10.1002/ps.7037
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to dicyclanil and imidacloprid in the sheep blowfly, Lucilia cuprina, in Australia

Abstract: Background The sheep blowfly, Lucila cuprina, is a myiasis‐causing parasite responsible for significant production losses and welfare issues for the Australian sheep industry. Control relies largely on the use of insecticides. The pyrimidine compound, dicyclanil, is the predominant control chemical, although other insecticides also are used, including imidacloprid, ivermectin, cyromazine and spinosad. We investigated in vitro resistance patterns and mechanisms in field‐collected blowfly strains. Results The Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the other hand, the responses of field strain larvae to ivermectin and spinosad were normally distributed, with the response of the susceptible reference strain falling within the distributions for the field strains for both chemicals. The existence of in vitro resistance to imidacloprid was reported by Kotze et al 40 who found that blowflies collected in the Walgett district of NSW showed resistance to both dicyclanil and imidacloprid in in vitro assays. This pattern of in vitro dicyclanil and imidacloprid resistance occurring together has subsequently been found in a further five strains collected from various regions across NSW (Kotze, unpubl.…”
Section: Sheep Blowflymentioning
confidence: 60%
See 1 more Smart Citation
“…On the other hand, the responses of field strain larvae to ivermectin and spinosad were normally distributed, with the response of the susceptible reference strain falling within the distributions for the field strains for both chemicals. The existence of in vitro resistance to imidacloprid was reported by Kotze et al 40 who found that blowflies collected in the Walgett district of NSW showed resistance to both dicyclanil and imidacloprid in in vitro assays. This pattern of in vitro dicyclanil and imidacloprid resistance occurring together has subsequently been found in a further five strains collected from various regions across NSW (Kotze, unpubl.…”
Section: Sheep Blowflymentioning
confidence: 60%
“…There has been considerable research on the molecular basis of chemical resistances in some of the parasites examined in the present study. This information would potentially allow for the development of molecular-based resistance tests (for example, nematodes, 55,56 cattle tick, 57,58 sheep blowfly 40 ). However, the use of this information on the molecular basis of resistance has been largely limited to basic research into mechanisms of resistance or small-scale surveys of resistance mechanisms in field-derived parasite samples, with no commercial tests available for Australian livestock producers.…”
Section: Resistance Testing Practicesmentioning
confidence: 99%